2009
DOI: 10.4314/ari.v5i3.48756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmodium species infections on packed cell volume of domestic chickens and helmeted guinea fowls in north eastern Nigeria

Abstract: Populations of exotic and indigenous domestic chickens and guinea fowls in northeastern Nigeria were surveyed for Plasmodium sp by examining their stained blood samples. The packed cel volumes of all blood samples were estimated. During the period of study (March to September 2006), rain a data were collected. The prevalence of Plasmodium in ect on in 575 domest c poultry examined was 9.4 % and the prevalence among the difference poultry types (exotic broilers and layers, indigenous chickens and guinea fowls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 10 publications
11
11
2
Order By: Relevance
“…Plasmodium parasites were not observed in the blood of the chickens examined. This result is in agreement [19], who also did not find Plasmodium parasites in domestic chickens in northeastern Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…Plasmodium parasites were not observed in the blood of the chickens examined. This result is in agreement [19], who also did not find Plasmodium parasites in domestic chickens in northeastern Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of avian haemosporidian in free-range chickens was found to be relatively higher in Dadin Kowa (7.3%), followed by Deba (5.3%), Kuri (4.5%) and Kwadon (4.0%), whereas Zambuk In the present study, Plasmodium species (13.8 %) was the most prevalent followed by Haemoproteus (6.8%) and Leucocytozoon (0.8%) in a single infection. This finding supported the report by Igbokwe et al [29], who reported that mosquitoes are endemic in northeastern Nigeria as the major vectors of Plasmodium species.…”
Section: No Of Chickens Examinedsupporting
confidence: 93%
“…free-range chickens in the study area. This result is higher than 11.4% reported in Borno[29], 19.56% reported in Kano[30],14 Citation: Jallailudeen Rabana Lawal., et al "Natural Infections of Avian Haemosporidian Parasites among Free-Range Chickens (Gallus gallus domesticus) in Yamaltu Deba, Gombe State, Nigeria". Acta Scientific Veterinary Sciences 2.4 (2020): 12-20.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The varying prevalence of these genera of avian haemoparasites has been previously reported in village chickens in developing countries including some parts of Nigeria [29][30][31][32][33][34]. These reports establish the occurrence of these avian haemoparasites in the poultry industries in Africa [35].…”
Section: Discussionsupporting
confidence: 56%